2019
DOI: 10.1016/j.scitotenv.2018.09.339
|View full text |Cite
|
Sign up to set email alerts
|

Linking bioavailability and toxicity changes of complex chemicals mixture to support decision making for remediation endpoint of contaminated soils

Abstract: A six-month laboratory scale study was carried out to investigate the effect of biochar and compost amendments on complex chemical mixtures of tar, heavy metals and metalloids in two genuine contaminated soils. An integrated approach, where organic and inorganic contaminants bioavailability and distribution changes, along with a range of microbiological indicators and ecotoxicological bioassays, was used to provide multiple lines of evidence to support the risk characterisation and assess the remediation end-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 74 publications
0
17
0
Order By: Relevance
“…Composting has been a successful bioremediation strategy in soils contaminated with PAHs, as well as with other pollutants, by providing organic substrates that stimulate the growth of potential microbial degraders and enhancing soil properties and quality (Antízar-Ladislao et al, 2006;Scelza et al, 2008;Covino et al, 2016;Jednak et al, 2017;Cipullo et al, 2019;Liu et al, 2019). However, few studies have considered composting or the addition of organic matter amendments to stimulate the microbial soil community, as a bioremediation strategy applied after the oxidative step (Satapanajaru et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Composting has been a successful bioremediation strategy in soils contaminated with PAHs, as well as with other pollutants, by providing organic substrates that stimulate the growth of potential microbial degraders and enhancing soil properties and quality (Antízar-Ladislao et al, 2006;Scelza et al, 2008;Covino et al, 2016;Jednak et al, 2017;Cipullo et al, 2019;Liu et al, 2019). However, few studies have considered composting or the addition of organic matter amendments to stimulate the microbial soil community, as a bioremediation strategy applied after the oxidative step (Satapanajaru et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…From the result presented in Table 2 revealed that iroko is more acidic than other and the magnitude order of acidicity is D > A > C > B. The results of present study revealed that the characterization and examination of physicochemical properties of functional components that control is helpful in monitoring, predicting and determination quality of respected area Cipullo et al, 2019;Frick et al, 2019;He et al, 2019;Kalhor et al, 2019;López-Vizcaíno et al, 2019;Mobbs et al, 2019;Rocha et al, 2019;Sivagami et al, 2019;Song et al, 2019;Ye et al, 2019), for the improvement of unwanted condition of contaminant in soil environment.…”
Section: Ph Valuesmentioning
confidence: 63%
“…A similar trend is also observed in many other studies which employ total concentration of contaminants for risk assessment and management of contaminated land, as well as exposure risks. Total concentration does not address partitioning and associated toxicological effects of the partitioned fractions, such as the bioavailable fraction, and therefore can be misleading in terms of risk assessment and contaminant management (Cipullo et al, 2019). Table 2 below shows some main advantages and advantages of using biochar, hydrogel, digestate and bioaugmentation for remediation purposes.…”
Section: Biochar: a Promising Panaceamentioning
confidence: 99%